MARKETING MIX ANALYSIS OF PURCHASING DECISIONS AT PT. AGRO PRIMA KAHATULISTIWA - Ardiansyah, Ardiansyah; Maulana, Muhammad Irfan; Sari, Wulan Purnama (Taksasila Edukasi Insani, 2023)
The purpose of this study was to determine the effect of the marketing mix on consumer decisions in buying a house in the housing of PT. Agro Prima Khatulistiwa Sintang District. The sampling technique used in this study was purposive sampling method with a sample of 94 people. The analysis technique used is simple linear regression analysis, correlation coefficient (R), coefficient of determination (R2), and model feasibility test. Based on the results of simple linear regression analysis, the regression equation or estimate is Ŷ = 2.804 + 0.879X . The results of the correlation coefficient analysis show that the relationship between the marketing mix and consumer purchasing decisions is very strong with an R value of 0.995. The results of the analysis of the coefficient of determination obtained an R Square value of 0.990, meaning that the contribution of the marketing mix variable to the variation in the ups and downs of consumer purchasing decisions in buying a house at PT. Agro Prima Khatulistiwa is 99.0% (1 x 0.990 x 100%) and the remaining 1% (1-0.990 x 100%) is influenced by other factors or variables not examined in this study. The results of the model feasibility test show the calculated F value of 9483.724 is greater than the Ftable value of 3.94 which means that a simple linear regression model can be used to predict consumer purchasing decisions that are influenced by the marketing mix.Keywords : Marketing Mix, Consumer Purchasing Decisions, Housing area